Transforming Personal Selling Through Qur'anic Ethical Principles In Marketing Communication - Syarifuddin, Syarifuddin (Program Studi Ekonomi Syariah, FEBI UIN Datokarama Palu, 2025)
Personal selling plays a central role in marketing communication, particularly in building long-term relationships with customers. However, existing approaches often emphasize transactional goals over ethical engagement, creating a gap between persuasive communication theory and its practical application in the field. This study aims to address this gap by integrating Qur’anic ethical principles qaulan baligha (effective speech), qaulan layyina (gentle speech), and qaulan karima (noble speech) into personal selling strategies. Using a qualitative approach based on library research and thematic interpretation of selected Qur’anic verses, the research constructs an ethical framework for communication in marketing. The findings demonstrate that each principle offers distinct communicative value: qaulan baligha enhances clarity and emotional depth, qaulan layyina fosters empathy and polite persuasion, and qaulan karima emphasizes dignity and respect. These values are mapped systematically to the stages of the personal selling process, from prospecting to follow-up, offering a structured and ethical alternative to conventional selling tactics. The study concludes that integrating Qur’anic principles into personal selling not only improves communicative effectiveness but also aligns marketing practices with spiritual and ethical values. This contributes to the development of Islamic marketing theory and provides practical guidance for marketers seeking to build trust, customer loyalty, and sustainable business relationships rooted in ethical communication. Future research is recommended to empirically validate the proposed model across different market contexts.